The Importance of Basic Financial Instruments Used in Islamic Banking (Texas Journal of Multidisciplinary Studies, 2023)
The article focuses mainly on the importance of basic financial instruments used in Islamic banking, the classification of Islamic financial instruments, and the definition of the instruments of mudoraba, murobaha, mushoraka.